The Homolidae of the Hawaiian Islands, with notes on the taxonomy of Moloha major (Kubo, 1936) (Crustacea: Decapoda: Brachyura) - Ng, Peter K. L.; Forges, Bertrand Richer De; Martin, Joel W. (Zootaxa, 2020)
Based partly on a collection of homolid crabs captured from baited traps in deep waters off French Frigate Shoals, Northwest Hawaiian Islands, in October 2006, the Hawaiian species of the family Homolidae are reviewed. Known genera and species in the Hawaiian Islands now include two species of Homola (H. orientalis and H. dickinsoni), two species of Lamoha (L. williamsi and L. personata), and five genera that are each represented by a single species (Paramola japonica, Moloha major, Yaldwynopsis hawaiiana, Latreillopsis okala, and Homologenus namakae). Seven of the 14 currently recognized genera of the Homolidae and nine of the 74 known species are now known from Hawaiian waters. Colour notes are included for the first time for two species (H. dickinsoni and Y. hawaiiana). A key to the family Homolidae in Hawaiian waters is included.